2018
DOI: 10.1113/jp275731
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem catecholaminergic neurones and breathing control during postnatal development in male and female rats

Abstract: The respiratory network undergoes significant development during the postnatal phase, including the maturation of the catecholaminergic (CA) system. However, postnatal development of this network and its effect on the control of pulmonary ventilation ( ) is not fully understood. We investigated the involvement of brainstem CA neurones in respiratory control during postnatal development [postnatal day (P)7-8, P14-15 and P20-21], in male and female rats, through chemical injury with conjugated saporin anti-dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 121 publications
(242 reference statements)
1
19
0
Order By: Relevance
“…A caveat of this method is that it does not consider body temperature for the estimation of tidal volume – a factor that has an effect on this parameter when the plethysmographic chamber is completely sealed (Drorbaugh & Fenn, ). Therefore, although the values of tidal volume of our vehicle‐treated control group were similar to other studies that used conventional whole‐body plethysmography (Patrone, Biancardi, Marques, Bicego, & Gargaglioni, ), we cannot exclude the possibility that the elevated tidal volume of pCIH rats relates to modifications in body temperature – a parameter that we did not evaluate in this study and that requires future experimental verification. However, we observed that the elevated tidal volume of pCIH animals was associated with a significant increase in inspiratory peak flow.…”
Section: Discussionmentioning
confidence: 66%
“…A caveat of this method is that it does not consider body temperature for the estimation of tidal volume – a factor that has an effect on this parameter when the plethysmographic chamber is completely sealed (Drorbaugh & Fenn, ). Therefore, although the values of tidal volume of our vehicle‐treated control group were similar to other studies that used conventional whole‐body plethysmography (Patrone, Biancardi, Marques, Bicego, & Gargaglioni, ), we cannot exclude the possibility that the elevated tidal volume of pCIH rats relates to modifications in body temperature – a parameter that we did not evaluate in this study and that requires future experimental verification. However, we observed that the elevated tidal volume of pCIH animals was associated with a significant increase in inspiratory peak flow.…”
Section: Discussionmentioning
confidence: 66%
“…DBH-sap has been previously validated as a NE-specific immunotoxin in intraventricular surgeries [34, 58, 59]. DBH IHC revealed a striking loss of fibers within PFC, as well as in adjacent cortical and subcortical regions, in DBH-sap (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Indeed, the monoaminergic systems play an important role in the control of breathing under resting conditions in most vertebrates (Gargaglioni et al, 2008). Previous studies from our laboratory have demonstrated that catecholaminergic neurons of the brainstem exert an inhibitory tonic effect on neonate rats and an inhibitory modulation under hypoxia and CO 2 exposure in males and females (Patrone et al, 2018(Patrone et al, , 2020. The role of DA in breathing control is related to its actions in both the peripheral chemoreceptors (López-Barneo et al, 2009) and in the brainstem nuclei (Kline et al, 2002).…”
Section: Introductionmentioning
confidence: 97%